(3GdJhQGIs
(3ChdgG (B:s
(3GdaUd GdSGHY jMUi ajg YOO hdO fhM s
(3BNQgG (B:s
(3CQSdg GdQH HYedgG HCQV eUQ ai aQYhf hLejY YHjOg hai LejY CQVg Hcd jO YRjRI hLejY GdBjGJ GdYXGe GdQi Yed ehSi HMVQI Bd ESQGFjd ced s
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3MGdI GdfSNI SjFI s
Keywords: (3GdOjGfGJ GdCNQis